FUNGSI DAN PERANAN BALI ORCHID GARDEN DI KESIMAN KERTALANGU SEBAGAI WISATA ALTERNATIF - I Made Budiasa (Bumi Lestari Journal of Environment, 2009)
As one of the world tourism destination, Bali is supported by tourism industry components, such as tourist attractions whether they are natural or cultural ones. As a good example of tourist attraction developed by a private company in Bali is Bali Orchid Garden. It is unique in term of its history, product, location, collection, promotion, personnel, and number of visitors. As a tourist attraction, the Bali Orchid Garden is quite relevant with the concept of alternative tourism, in which it is opposed to mass tourism. The alternative tourism lies emphasis on the small scale of development, the active experience of tourists, direct contact between tourists and host community, local community prosperity, providing tourists with a wider choice of tourist products to enjoy, and it cares in preserving the environment. Related to the main function of Bali Orchid Garden as a tourist attraction, its role is to provide a product diversification or innovation to support cultural tourism in Bali. In a wider perspective, the role and function of Bali Orchid Garden could be seen from economic, socio-cultural, and environmental aspects